Searching for potential marine sand resources to mitigate beach erosion in island settings. Issue 5 (4th May 2021) - Hasiotis, Thomas; Gazis, Iason-Zois; Anastasatou, Marianthi; Manoutsoglou, Evangelia; Velegrakis, Adonis F.; Kapsimalis, Vasileios; Karditsa, Aikaterini; Stamatakis, Michael
Abstract: This article presents the results of a marine geophysical and sedimentological study carried out around Lesvos Island (NE Aegean) to investigate the potential of exploitable marine aggregate (MA) deposits that could be used for beach replenishment purposes. Sub-bottom profiler data showed a good prospect for potential coarse-grained deposits in two of the three surveyed areas around Lesvos. Grain size and mineralogical analysis of the surficial sediments revealed sands that could properly feed nourishment schemes for eroded beaches or artificial beach development. Observed MA volumes are considered adequate for renourishment operations, when the threat of projected sea-level rise is introduced. Environmental constraints, as well as human activities, are considered for the suggestion and prioritization of specific areas for detailed surveying before future exploitation.